Characterization of EBT3 radiochromic films for dosimetry of proton beams in the presence of magnetic fields. Issue 7 (31st May 2019) - Padilla‐Cabal, Fatima; Kuess, Peter; Georg, Dietmar; Palmans, Hugo; Fetty, Lukas; Fuchs, Hermann
Abstract : Purpose: Radiochromic film dosimetry is extensively used for quality assurance in photon and proton beam therapy. So far, GafchromicTM EBT3 film appears as a strong candidate to be used in future magnetic resonance (MR) based therapy systems. The response of Gafchromic EBT3 films in the presence of magnetic fields has already been addressed for different MR‐linacs systems. However, a detailed evaluation of the influence of external magnetic fields on the film response and calibration curves for proton therapy has not yet been reported. This study aims to determine the dose responses of EBT3 films for clinical proton beams exposed to magnetic field strengths up to 1 T in order to investigate the feasibility of EBT3 film as an accurate dosimetric tool for a future MR particle therapy system (MRPT). Methods: The dosimetric characteristics of EBT3 films were studied for a proton beam passing through magnetic field strengths of B = 0, 0.5, and 1 T. Absorbed dose calibration and measurements were performed using clinical proton beams in the nominal energy range of 62.4–252.6 MeV. Irradiations were done using an in‐house developed PMMA slab phantom placed in the center of a dipole research magnet. Monte Carlo (MC) simulations using the GATE/Geant4 toolkit were performed to predict the effect of magnetic fields on the energy deposited by proton beams in the phantom. Planned and measured doses from 3D box cube irradiations were compared to assess the accuracy of the dosimetric method using EBT3 films with/without the external magnetic field. Results: Neither for the mean pixel value nor for the net optical density, any significant deviations were observed due to the presence of an external magnetic field (B ≤ 1T) for doses up to 10 Gy. Dose‐response curves for the red channel were fitted by a three‐parameter function for the field‐free case and for B = 1T, showing for both cases an R‐square coefficient of unity and almost identical fitting parameters. Independently of the magnetic field, EBT3 films showed an under‐response as high as 8% in the Bragg peak region, similarly to previously reported effects for particle therapy. No noticeable influence of the magnetic field strength was observed on the quenching effect of the EBT3 films. Conclusions: For the first time detailed absorbed dose calibrations of EBT3 films for proton beams in magnetic field regions were performed. Results showed that EBT3 films represent an attractive solution for the dosimetry of a future MRPT system. As film response functions for protons are not affected by the magnetic field strenght, they can be used for further investigations to evaluate the dosimetric effects induced due to particle beams bending in magnetic fields regions.